Intrinsic angular momentum for radiating spacetimes which agrees with the Komar integral in the axisymmetric case - Gallo, Emanuel (2014)
Fil: Gallo, Emanuel. Universidad Nacional de Córdoba. Facultad de Matemática, Astronomía y Física; Argentina.